Suppression of inrush current of three-phase transformer based on pre-magnetization principle - Wu, Yucai; Liu, Yanze; Tan, Yaokun; Zhang, Shaojiu; Jiang, Yi; Huang, Chenhui; Li, Yingfeng; Zhang, Zhiming (Dianji yu Kongzhi Xuebao = Electric Machines and Control, 2025)
Excitation inrush current can not only cause misoperation of transformer differential protection, but also cause tripping of nearby normally operating equipments such as transformers and motors. Effective suppression of excitation inrush current is of great significance. The expression of the main magnetic flux was derived in the core during the no-load closing process of the transformer. It is found that the residual magnetism of the core to some extent affects the amplitude of the free component in the magnetic flux expression. When the magnitude and direction of the residual magnetism are appropriate, the free component of the magnetic flux can be completely eliminated, thereby reducing the excitation inrush current of the no-load closing to zero. Subsequently, simulation verification was conducted on a 500 kV three-phase double winding transformer group, and further experimental verification was completed on a 15 kVA three-phase autotransformer group, demonstrating that pre magnetization of the core can significantly reduce the excitation inrush current during the no-load closing process of the transformer. This method not only helps prevent misoperation of differential protection but also significantly reduces the risk of nearby equipment tripping.